The effect of SGLT2 inhibitor in patients with type 2 diabetes and atrial fibrillation - Yongin Cho; Sung-Hee Shin; Min-Ae Park; Young Ju Suh; Sojeong Park; Ji-Hun Jang; Dae-Young Kim; So Hun Kim (PLoS ONE, 2025)
Background Sodium glucose cotransporter 2 (SGLT2) inhibitors improve clinical outcomes in several populations including type 2 diabetes (T2D), chronic renal insufficiency, and heart failure (HF). However, limited data exist on their effects on atrial fibrillation (AF). Methods We conducted a retrospective cohort study using the National Health Insurance Service database. A total of 4,771 patients with T2D and AF who were newly prescribed SGLT2 inhibitors or DPP4 inhibitors were selected and matched in a 1:2 ratio by propensity score with 37 confounding variables. We assessed the effect of SGLT2 inhibitors on the composite outcome of either HF hospitalization or death. Results Over a median follow-up of 31 months, patients on SGLT2 inhibitors were associated with a lower risk of hospitalizations for HF or mortality compared to those on DPP4 inhibitors (HR 0.61; 95% CI 0.44–0.85; P = 0.004). SGLT2 inhibitor use was also associated with a lower risk of mortality (HR 0.61; 95% CI 0.39–0.94; P = 0.025) and CV mortality (HR 0.43; 95% CI 0.21–0.86; P = 0.018), but not of MI (HR 1.22 [95% CI 0.72–2.09]; P = 0.461) or stroke (HR 1.00 [95% CI 0.75–1.33]; P = 0.980). The incidence of hospitalizations for HF, although statistically insignificant, tended to be lower in the SGLT2 inhibitor group (HR 0.63 [95% CI 0.39–1.02]; P = 0.062). Conclusion In a nationwide cohort of patients with T2D and AF, SGLT2 inhibitor was associated with a lower risk of mortality, which may suggest that SGLT2 inhibitors may be considered as the first-line antidiabetic medication in patients with T2D and AF.